Selective nitric oxide electroreduction at monodispersed transition-metal sites with atomically precise coordination environment - Zhao, Siwen (2023)
Mitigating nitrogen oxide emissions is critical to tackling global warming and improving air quality. Electrochemically converting nitrogen oxide pollutants into value-added fuels such as ammonia (NH3) and hydroxylamine (NH2OH) is of great significance, yet the efficiency is hindered by complex reaction pathways and sluggish kinetics. Here, we demonstrated monodispersed transition-metal sites, e.g., iron (Fe) and nickel (Ni), with atomically precise coordination environments to electrocatalyze nitric oxide conversion with remarkable selectivity, activity, and durability. We observed that metal centers strongly regulate the nitrogen-product distribution. In particular, Ni preferred NH3 production with a high yield rate of 1.6 mmol mg−1 h−1, whereas Fe exhibited a superior selectivity toward NH2OH, approaching a record-high production rate of 3.1 mmol mg−1 h−1 with a selectivity of 83.5%. Operando Fourier transform infrared spectroscopy revealed different NO adsorption capabilities of single-atomic Ni and Fe, which can well explain the different reduction pathways according to the theoretical calculations.